2013
DOI: 10.1111/imj.12178
|View full text |Cite
|
Sign up to set email alerts
|

Survival times of women with metastatic breast cancer starting first‐line chemotherapy in routine clinical practice versus contemporary randomised trials

Abstract: Median and better survival times in routine practice were similar to those from randomised clinical trials; however, survival times worse than the median were shorter, likely reflecting patient selection in trials. Oncologists should adjust trial-based survival estimates for patients not meeting typical trial eligibility criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…From the patient's perspective, this uncertainty is psychologically distressing. [10][11][12] Studies suggest that a lack of insight into disease status and prognosis can lead to poorer outcomes among patients with advanced or incurable cancer, with psychological consequences including increased mistrust and feelings of abandonment. 12,13 Furthermore, the cancer-free implication of an NED status is clearly a strongly desired outcome for any patient with MBC, and validation of the frequency with which this status occurs is influential.…”
Section: Introductionmentioning
confidence: 99%
“…From the patient's perspective, this uncertainty is psychologically distressing. [10][11][12] Studies suggest that a lack of insight into disease status and prognosis can lead to poorer outcomes among patients with advanced or incurable cancer, with psychological consequences including increased mistrust and feelings of abandonment. 12,13 Furthermore, the cancer-free implication of an NED status is clearly a strongly desired outcome for any patient with MBC, and validation of the frequency with which this status occurs is influential.…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal et al reported an 81.8 months median overall survival for TNBC patients [11]. The overall survival of a metastatic TNBC patient is 18 months from the diagnosis of the metastasis [4,12,13]. Our patient lived 89 months after her first diagnosis of TNBC (25 months with stage IV disease).…”
Section: Discussionmentioning
confidence: 67%
“…In a single institution study of 2091 mBC patients, Dawood et al 17 reported a 44% decreased risk of death among patients with HER2/neupositive disease treated with trastuzumab as first-line therapy compared to HER2/neu-negative patients. Similarly, in a separate study of mBC patients initiating first-line chemotherapy at a single oncology clinic, Thientosapol and colleagues found that mBC patients with HER2þ tumors lived significantly longer than patients with HER2-negative tumors (HR ¼ 0.49, CI 0.34-0.72, p50.001), reflecting positive responses to HER2-targeted agents 18 . A potential reason for this discrepancy is that the study populations were defined differently.…”
Section: Discussionmentioning
confidence: 93%